2020
DOI: 10.1007/978-3-030-57993-7_65
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependencies of Quality Management, Knowledge Management and Innovation Performance. A Literature Review

Abstract: Quality management should represent one of the most common approaches to improving quality and innovation performance. Still, it is shown that this is not always the case. To find the real cause of the contradictory results, a literature review was conducted. Some authors propose that knowledge management might present the missing link between quality management and innovation performance. Therefore, in this research, the importance of knowledge management will be considered, as a key mediator between quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, KM has every potential to improve the company's innovative potential which is a critical factor of competitive advantage for an organization. According to Zizakov et al [56], for the ability of a company to develop new products, the process of workflow is highly dependent on efficient KM practices. Thus, KM creates a footing for enterprises to become more advanced and competitive in the market.…”
Section: Knowledge Management and Organizational Sustainabilitymentioning
confidence: 99%
“…Moreover, KM has every potential to improve the company's innovative potential which is a critical factor of competitive advantage for an organization. According to Zizakov et al [56], for the ability of a company to develop new products, the process of workflow is highly dependent on efficient KM practices. Thus, KM creates a footing for enterprises to become more advanced and competitive in the market.…”
Section: Knowledge Management and Organizational Sustainabilitymentioning
confidence: 99%
“…Several studies presented the same results and contended that quality management could be one of the prerequisites for innovation [14][15][16][17]. However, some authors claim the opposite [13,18,[21][22][23] and debate the influence of quality management on innovation [22,24,25]. Innovation can be observed as product innovation and process innovation.…”
Section: Introductionmentioning
confidence: 95%
“…Secondly, when observing KM, the literature review concluded that the factors with the highest frequency are knowledge creation, knowledge application, and knowledge dissemination [25]. Therefore, the research model sets these factors as second-order constructs.…”
Section: Knowledge Managementmentioning
confidence: 99%
See 2 more Smart Citations